2011
DOI: 10.1007/s00432-011-1032-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the vascular damaging agents DMXAA and ZD6126 on hypericin distribution and accumulation in RIF-1 tumors

Abstract: We conclude that HYP accumulation is optimal when it is administered after VDA injection. We also found that HYP accumulation in necrosis is not changed when using VDAs with different working mechanisms. This insight provides a rationale for tumor necrosis therapy (TNT) using iodine-131-labeled hypericin ([(131)I]-HYP) in combination with VDAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
0
10
1
Order By: Relevance
“…In support of our hypothesis, we observed increased drug delivery following pretreatment of tumors with VDA (2 hours prior to chemotherapy administration). In support of this approach, Marysael et al, have previously reported increased accumulation of the necrosis avid agent, Hypericin, when administered 24 hours after treatment with DMXAA (33). In our study, enhancement of therapeutic efficacy was dependent on the VDA dose employed.…”
Section: Discussionmentioning
confidence: 94%
“…In support of our hypothesis, we observed increased drug delivery following pretreatment of tumors with VDA (2 hours prior to chemotherapy administration). In support of this approach, Marysael et al, have previously reported increased accumulation of the necrosis avid agent, Hypericin, when administered 24 hours after treatment with DMXAA (33). In our study, enhancement of therapeutic efficacy was dependent on the VDA dose employed.…”
Section: Discussionmentioning
confidence: 94%
“…However, preclinical studies suggest that following exposure to a VDA, only the center of the tumor becomes necrotic, with a viable rim remaining in the periphery. This rim of viable tumor cells is highly proliferative and has potential for tumor growth [20]. This phenomenon provides the rationale for developing combination therapy with VDAs and anti-angiogenesis or conventional cytotoxic drugs [21].…”
Section: Vascular Disrupting Agents (Vdas)mentioning
confidence: 99%
“…1,3,4) 42,87,88. The engineered design for SMSDTTS that combines sequential intravenous injection of CA4P and 131 I-Hyp at a 24h interval is believed advantageous for the following considerations: a) being both naturally derived small molecules allowing systemic injections with much better accessibility to targeted tissues, CA4P and Hyp (in the form of its radiolabeled iodo-derivative) share a highly targeting capacity but diverse and complementary specificities; b) massive intra-tumoral necrosis induced by CA4P serves as a target or anchor for 131 I-Hyp; c) a 24h interval between CA4P and 131 I-Hyp allows the complete formation of necrosis, meanwhile optimal accessibility to the latter due to partial recovery of tumor vascularization 89; d) iodine-131 that emits tumoricidal beta particles and gamma rays useful for scintigraphy provides a theragnostic solution for malignancies; e) being spatially or geographically cooperational, CA4P kills tumor cells inside out, whereas 131 I-Hyp eradicates the remnant tumor cells on the periphery. Micro-geographically, 131 I-Hyp accumulates with high concentration into the necrotic tissue neighboring the viable cancer cells.…”
Section: Engineered Designs With Smsdttsmentioning
confidence: 99%